2004
DOI: 10.1007/s00466-003-0522-4
|View full text |Cite
|
Sign up to set email alerts
|

A numerical analysis of free-surface flow in curved open channel with velocity?pressure-free-surface correction

Abstract: This paper presents a numerical study on free-surface flow in curved open channel. An improved SIMPLEC algorithm with velocity-pressure-free-surface coupled correction is developed and validated. Such algorithm differs from the traditional SIMPLEC algorithm and includes three correction equations which are named as the velocity correction equation, the freesurface correction equation derived from the continuity equation with the kinematic boundary conditions on the free-surface and the bottom bed, and the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Booij (2003) reported the existence of a minor secondary flow at the outer wall and claimed that such flow leads to the local scour at outer wall in the form of wash underneath. Lu et al (2004) applied a threedimensional numerical model to simulate flow pattern at a 180° bend using the standard   k turbulence model. They showed an acceptable agreement between the results obtained from the numerical model and experimental data; but their numerical model was not capable of predicting minor secondary rotational cell in the outer wall.…”
Section: Introductionmentioning
confidence: 99%
“…Booij (2003) reported the existence of a minor secondary flow at the outer wall and claimed that such flow leads to the local scour at outer wall in the form of wash underneath. Lu et al (2004) applied a threedimensional numerical model to simulate flow pattern at a 180° bend using the standard   k turbulence model. They showed an acceptable agreement between the results obtained from the numerical model and experimental data; but their numerical model was not capable of predicting minor secondary rotational cell in the outer wall.…”
Section: Introductionmentioning
confidence: 99%
“…According to Chang (1984), even for small curves without flow separation, flow resistance or the energy cost caused by transverse flow can be extremely large. Many researchers have studied flow dynamics in a wide variety of channel bend configurations using various methods owing to the major significance of this content (Tominaga and Nagao, 2000;Blanckaert and Graf, 2001;Booij, 2003;Blanckaert and De Vriend, 2004;Lu et al, 2004;Bodnar and Prihoda, 2006;Roca et al, 2007;Blanckaert, 2009;Zhou et al 2009). These studies aim to collect data on flow variables in channel bends and analysis of the results that have provided the knowledge base for understanding the bend flows.…”
Section: Introductionmentioning
confidence: 99%
“…At the top of the bend, the longitudinal average velocity distribution is close to a parabola, and the maximum point is below the water surface, and the overall average velocity is large on the top and small on the bottom [3]. erefore, many scholars [4][5][6][7] have studied the movement of secondary flow, the change of water depth in transverse and longitudinal direction, and the distribution of bed shear force in the bend and found that there are multiple vortices in the secondary flow in the continuous bend, and there is a region of secondary flow direction reversal near the riverbed. e secondary flow also affects the redistribution of downstream velocity, and the transport of secondary flow also affects the redistribution of bed shear stress.…”
Section: Introductionmentioning
confidence: 99%